Minutes of Executive meeting. 23 May 1992 - British Association for Irish Studies, BAIS; McAuley, Jim (1992)
Typescript minutes of meeting of the Executive of British Association for Irish Studies (BAIS). With a covering letter from Dr. James W. [Jim] McAuley (Honorary Secretary) dated 26 June 1992 advising Executive members of the next meeting (with manuscript annotations).